Atmospheric convection over complex terrain and urban canopy: Non-local ventilation mechanisms and application to pollution-dispersion and air-quality problems - Zilitinkevich, Sergej S.; Hunt, J. C.R.; Grachev, A. A.; Esau, I. N.; Lalas, D. P.; Akylas, Evangelos; Tombrou, M.; Fairall, C. W.; Fernando, H. J.S.; Baklanov, A.; Joffre, S. M. (My University, 2007)
modern atmosphere-hydrosphere-biosphere model chains, convective boundary-layer models and parameterization packages represent the most important coupling agents, which essentially control the overall quality of predictions from coupled models. This paper focuses on the enhancement of turbulent mixing due to large-scale semi-organized eddies and interactions between large eddies and surface roughness elements up to very high obstacles such as buildings, rocks and hills. Large-scale structures in the shear-free convective boundary layers consist of strong plumes and wider but weaker downdraughts. Close to the surface they cause local "convective winds" blowing towards the plume axes. The latter generate turbulence, in addition to its generation by the buoyancy forces, and strongly contribute to the turbulent fluxes of heat and other scalars. This mechanism is especially important over very rough surfaces. The proposed model is validated against data from measurements over different sites and also through large-eddy simulation (LES) of convective boundary layers (CBLs) over a range of surfaces from very smooth to extremely rough. Excellent correspondence between model results, field observations and large-eddy simulations is achieved. The obtained resistance and heat/mass transfer laws are recommended for practical use inmeso-scale, weatherprediction, climate and other environmental models. © Springer 2007.
Keywords: Convection; Environmental modeling; Semi-organized eddies; Surface fluxes